Practicing as knowing: The epistemological significance of practices, exemplified with funerary practices - Schmidt, Ulla (Studia theologica, 2021)
This article investigates how practices and practicing are also ways of knowing and knowledge and thus epistemologically generative. Drawing on philosophy of religion, practical-theological ideas of practical wisdom, as well as sociological practice theory, it argues that practices are sites of generating and acquiring basic epistemic skills of perception and forming beliefs. But even more, they are shared forms of knowing since they provide socially, materially and bodily distributed interpretations of objects, persons and abstracts and their import, circulating knowledge of how to do and perform practices, and an understanding of the objectives of practices and their emotive significance. This is then exemplified with certain aspects of funerals, analysing how they are cultural and religious sedimentations of knowing death and mortality.